Effect of Leaching Temperature on Lithium Recovery fromLi-Montmorillonite (Bledug Kuwu's Mud). (February 2019) - Lalasari, L H; Rohmah, M; Setiawan, I; Natasha, N C; Andriyah, L; Arini, T; Firdiyono, F; Wahyuadi, J
Abstract: The availability of lithium resources in the world is important along with the development of electronic technology and electrical transportation, especially lithium batteries. In Indonesia, lithium is found in brine associated with hot spring, clay associated with a geothermal activity, and spodumene minerals. The Bledug Kuwu's Mud contained a Li-Montmorillonite phase with lithium content that was 0.0029%. For lithium recovery, Li-Montmorillonite was leached with distilled water on the S / L ratio was 1: 2 for 3 hours. In this experiment, the leaching temperature was varied as follows: 25°C, 30°C, 35°C, and 45°C. Experimental results showed that lithium recovery from Li-Montmorillonite was successfully carried out by water leaching at atmospheric pressure. This result was supported by XRD analysis on residues. It indicated that there was no Li-Montmorillonite phase at the residues. The highest percentage of lithium recoveries in this research obtained at leaching temperature of 25°C was 87.2% (15.78 ppm).